Women’s Post-Divorce Rights in Malaysian and Indonesian’s Court Decisions - abd rahman dahlan; Fathinuddin Fathinuddin; Azizah Azizah; Nur Rohim Yunus; Aliyeva Patimat Shapiulayevna; Yunasril Ali (AHKAM : Jurnal Ilmu Syariah, 2023)
Indonesia and Malaysia are predominantly Muslim and belong to the Shafii school of thought. Both have similarities concerning the rights of the wife in divorce. This study examines the fulfilment of post-divorce rights for women based on the decisions of the Religious Courts in Indonesia and Malaysia. The period for this research object is limited to 2014-2016. The research used a qualitative method with comparative and case approaches. This study finds that, legally, a wife can receive post-divorce rights, including ‘iddah, mut‘ah and ḥaḍānah. However, the Indonesian and Malaysian courts’ decisions regarding women’s post-divorce rights differ depending on whether the women request the fulfilment of their rights in their petitions. In Indonesia, judges can use their ex-officio rights to grant women their rights even without their requests. In Malaysia, on the other hand, the wives must state their demands in their petitions.  Abstrak: Indonesia dan Malaysia adalah negara mayoritas berpenduduk muslim dan bermazhab Syafi’i. Keduanya memiliki persamaan berkaitan dengan hak- hak isteri dalam perceraian. Penelitian ini bertujuan untuk mengetahui hak-hak isteri dalam perceraian berdasarkan putusan-putusan Pengadilan Agama di Indonesia, dalam hal ini Pengadilan Agama Jakarta Selatan dan Mahkamah Syariah di Malaysia. Kurun waktu objek penelitian ini dibatasi tahun 2014- 2016. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan komparatif dan pendekatan perundang-undangan. Hasil penelitian menyatakan bahwa hak-hak yang dapat diterima isteri dalam perceraian yaitu hak nafkah ‘iddah, mut‘ah dan ḥaḍānah. Namun dalam kenyataan, putusan pengadilan tentang hak-hak isteri dalam perceraian di Indonesia dan Malaysia terjadi perbedaan. Perbedaan putusan tersebut terjadi dalam hal isteri pada proses persidangan tidak memohon atau menuntut hak-haknya kepada majelis hakim. Di Indonesia, hakim memiliki hak ex officio. Hakim memberi hak- hak isteri, meskipun isteri tidak menuntut hak-haknya selama temohon selalu hadir dalam persidangan. Di Malaysia, hak-hak isteri harus diminta kepada majelis hakim oleh isteri, karena perceraian merupakan permohonan dan kesepakatan antara para pihak.